Case Report: Exceptional Response to Avelumab After Failure of Electrochemotherapy in a Patient With Rapidly Progressive, PD-L1-Negative Merkel Cell Carcinoma - Torchio, Martina; Cattaneo, Laura; Milione, Massimo; Prinzi, Natalie; Corti, Francesca; Ungari, Marco; Anichini, Andrea; Mortarini, Roberta; Occhini, Antonio; Bertino, Giulia; Maurichi, Andrea; Coppa, Jorgelina; et al. (Frontiers in Oncology, 2021)
This case report shows, for the first time, a patient experiencing a complete response after one dose of avelumab following extensive disease progression with prior electrochemotherapy (ECT) treatment. We suggest that ECT may help to establish a tumor microenvironment favorable to immunotherapy. Merkel cell carcinoma (MCC) is a highly aggressive skin cancer with seldom durable chemotherapy responses. ECT has recently emerged as a potential treatment option for several malignancies, including MCC. Avelumab, an anti-programmed cell death-ligand 1 (PD-L1) monoclonal antibody, became the first approved treatment for patients with metastatic MCC. ECT has been shown to activate the immune response, but it is still unknown how ECT may affect patient’s response to subsequent immunotherapy. We report a case of a patient with MCC who presented with a rapidly growing skin nodule of the right cheek and experienced extensive disease progression following surgical debulking and ECT treatment. The patient received a flat dose of 800 mg avelumab intravenously every 2 weeks showing complete tumor regression after only 1 dose. Immunohistochemical analysis of surgical and post-ECT biopsies collected from the primary lesion revealed tumor expression of programmed cell death protein-1 (PD-1), but not PD-L1. Analysis of the tumor samples also revealed no expression of Merkel cell polyomavirus (MCPyV). Comparison of the biopsies showed a decrease in myeloid and T-cell markers after ECT but an increase in major histocompatibility complex (MHC) class I expression on tumor cells. Additionally, the patient experienced an increase in neutrophil-to-lymphocyte ratio and lactate dehydrogenase values post-ECT, which subsequently decreased with avelumab treatment. As of 30 October 2019, the patient was still receiving avelumab treatment and had an ongoing complete response. In this case report, a patient with PD-L1-negative and MCPyV-negative MCC who had disease progression following ECT experienced complete tumor regression with avelumab treatment, suggesting, for the first time to our knowledge, that ECT may help to establish a tumor microenvironment favorable to immunotherapy via a potential abscopal effect. Tumor-intrinsic PD-1 expression and modulation of MHC class I antigens after ECT may contribute to the clinical efficacy of avelumab in this context.